O atendimento a envolvidos em violência: concepções de psicólogos sobre gênero e violência conjugal - Oliveira, Danielle Cristina de (2005)
The Feminist Movement contributed to the public debate on gender and conjugal violence. Conjugal violence has been discussed from the dualist conception: man-aggressor versus woman-victim and understood as violence against women. The emergence of academic works which analyzed conjugal violence by theoretical approaches, and that contested this dualist view, made possible the understanding of the subject by means of the multiple roles of men and women in a violent affective relation. The relational referential does not ignore the cultural productions on gender and ethnicity, which produce differences of power within the couple, although defends that the comprehension of violence between partners cannot be reduced to the idea of feminine subalternity. Considering these contexts, this study investigated conceptions on gender and conjugal violence of the nine psychologists who worked in public programs that assist those involved in conjugal violence in Greater Vitória, ES, Brazil, by means of a semi-structured interview that covered the following themes: psychological assistance, gender, conjugality, and conjugal violence. The psychological practices were characterized by a diversity of assistances: clinical assistances, the couple s therapy, the psychological orientation, the groups therapy, and practices in cooperation with other specialties, mainly law and social service. The main meanings were highlighted: gender was considered a relation of power between men and women, socially constructed, still strongly influenced by the traditional roles of man provider and woman nurturer. In general, conjugal violence is understood as a process of oppression mediated by an unequal power between men and women, expressed by physical and psychological aggression. The psychologists assume, therefore, a pro-feminist posture, existing basically two styles of action. One part develops actions with reference to the principles of the feminist movement, assuming exclusively a role of defense of the battered women; these interviewees assist predominantly women and demonstrate in their speeches clear influences of the dualist conception. The other group of psychologists also consider the non-symmetries between genders, but constructs the psychological practices by the mediation of conflicts between men and women, clearly considering the costs of the gender charge and the consequences of conjugal violence for men and women approaching the relational referential.